Bicarbonate transporters in male fertility: identification and functionality in testicular cells - Bernardino, Raquel Alexandra Lages (2013)
The formation of competent spermatozoa is a complex event that depends on the establishment of adequate environments throughout the male reproductive tract. The maintenance of a proper ionic content in the luminal milieus is crucial for spermatozoa maturation. Bicarbonate is not only essential to ionic homeostasis, as HCO3 - concentration plays an essential role in the pH maintenance along the male reproductive tract. Diabetes mellitus (DM) is one the most prominent public health threats in modern societies and its incidence is drastically increasing in men with reproductive age. This metabolic disease is characterized by hyperglycaemia that can result from defects in insulin secretion and/or insulin action. There are two types of DM, type-1 DM and type-2 DM (T2DM). T2DM is referred to as non-insulin-dependent diabetes, and encompasses individuals who have insulin resistance and usually have a relative insufficient insulin secretion. This type of diabetes can be prevented if detected early, in a status called pre-diabetes, which usually precedes the appearance of the disease. It has been reported that DM alters pHi regulation in mammalian cells mainly by markedly altering the activity in some ion transporters, particularly some bicarbonatedependent mechanisms. Little is known on the effects of this pathology on the membrane transport mechanisms involved in pH regulation on male reproductive tract cells and even fewer on the effects of the different stages involved in the progression of this pathology, particularly during pre-diabetes. The first objective of this work was to analyse possible alterations on the levels of the most relevant bicarbonate transporters of the Slc4 family (anion exchanger 2 -AE2; Na+ -driven Cl- /HCO3 - exchanger - NDCBE; electrogenic Na+ /HCO3 - co-transporter 1- NBCe1; electroneutral Na+ /HCO3 - co-transporter 1 - NBCn1) in testis and epididymis of a pre-diabetic animal model. Protein and mRNA expression levels were evaluated by western blot and real-time PCR, respectively. We were able to confirm the presence of all the bicarbonate transporters of the Slc4 family studied both in testis and epididymis. At testicular level, although no alterations were detected in protein expression, the mRNA levels of NBCe1, NBCn1 and NDCBE were significantly increased in pre-diabetic animals. On the other hand, at epididymal level, prediabetes caused a significant increase on AE2 protein levels and a significant decrease of NDCBE protein levels. Hence, these alterations might translate into changes of the HCO3 − transepithelial epididymal fluxes in vivo, which might represent a threat for sperm survival during storage in the epididymis. Our results might correlate with previous results that reported a significant increase in abnormal sperm morphology in pre-diabetic rats. Furthermore, as several studies support an association of men with higher 17βestradiol (E2) levels and the increased risk of diabetes and, moreover, E2 is responsible for the modulation of the expression of specific ion transporters in the male reproductive tract, the second objective of our work was to determine the effect of this sex steroid hormone on the expression and functionality of selected bicarbonate transporters of the Slc4 family in cultured Sertoli cells (SCs). All the selected four transporters were identified and quantified in SCs (using RT-PCR and real time PCR, respectively). In cells treated with E2 (100 nM) a significant increase in mRNA expression levels of AE2, NBCn1 and NBCe1 was observed. Subsequently, we also evaluated the effect of E2 (100 nM) on transcellular transport in SCs, grown in semi-permeable supports, using the Voltage-Clamp technique. E2-treated SCs presented a significant alteration on the shift of the short-circuit current (∆Isc) induced by ATP, as well as on short-circuit current (Isc) recovery after stimulation. These alterations may be promoted by the increase of AE2 mRNA levels observed in E2-treated cells, as in these cells the Isc involves the secretion of Clthrough the apical membrane by an ATP-activated Clconductance and its absorption via HCO3 − -dependent mechanisms through the basolateral membrane. An increase on AE2 levels will surely be responsible for a prompter effect of this transporter on Isc variation following ATP activation. Thus, our results show a relation of the pre-diabetes, as well as increased E2 levels, with the expression/function of bicarbonate transporters in rat epididymis and SCs, providing new evidence on the mechanisms by which this prodromal stage of DM and its associated features can affect male reproductive function.